Pengaruh Proses Pengolahan Terhadap Kadar Beta Karoten Pada Ubi Jalar Varietas Ungu (Ipomoea Batatas (L.) Lam) dengan Metode Spektrofotometri Visibel - Fitra Fauziah; Roslinda Rasyid; Reza Fadhlany (Jurnal Farmasi Higea, 2015)
Purple sweet potato (Ipomoea batatas) is one of the agricultural commodities as source of carbohydrates and energy which is included in the family of Convolvulaceae. It is also a good source of vitamins and minerals which is good for nutrition and health. One of the compounds contained in purple sweet potato is beta-carotene. Beta-carotene is a precursor of vitamin A. It is useful as an antioxidant, boosts the immune system and treats other diseases. Beta-carotene is unstable, especially at high temperature. This study aims at answering the question as to how the processing of purple sweet potato can effect to beta-carotene level by using Visible spectrophotometry method. This study is conducted by performing three treatments to purple sweet potato i.e. raw, fried and boiled sample. Weight of raw sample is 10 grams,  fried and boiled sample is 15 grams. The sample were extracted by liquid-liquid extraction and it is measured by Visibel spectrophotometer at maximum wavelength of 452.5 nm. The results obtained show that the average level of beta-carotene is 75.91 ±1.92 ppm for raw samples, 63.05 ± 3.45 ppm for fried, and 45.66 ± 0.82 ppm for boiled. The result is statistically calculated by one-way ANOVA statistical analysis. It shows that sig 0.000 (P < 0.05), and it indicates that there is an effect of processing to the average level of beta-carotene contained in purple sweet potato.